Development of an evanescent optical integrated sensor in the mid-infrared for detection of pollution in groundwater or seawater. (2nd October 2017) - Baudet, E.; Gutierrez-Arroyo, A.; Baillieul, M.; Charrier, J.; Němec, P.; Bodiou, L.; Lemaitre, J.; Rinnert, E.; Michel, K.; Bureau, B.; Adam, J. L.; Nazabal, V.
Abstract: The detection of molecules dissolved in liquid medium can be envisaged by means of an optical integrated sensor operating in middle infrared range. The intended sensor is composed of a cladding and a guiding selenide sputtered layers transparent in middle infrared. Hence, Ge-Sb-Se thin films were selected in view of tailored refractive index contrast, successfully deposited by radio frequency magnetron sputtering and characterized. To maximize the evanescent field at a wavelength of 7.7 µm, a suitable selenide waveguide allowing measuring the optical transmitted power was designed by performing computer simulations based on the effective index method enabling single-mode propagation for a waveguide width between 8 and 12 µm. Selenide sputtered films were micro-patterned using reactive ion etching with inductively coupled plasma process. Finally, optical waveguide surface was functionalized by the deposition of a hydrophobic polymer, which will permit detection of organic molecules in water.